A new approach to development banking in Jamaica - Collister, Keith R. (CEPAL SantiagoCL, 2007)
Analyzes development banking in Jamaica, identifies its weaknesses and proposes solutions to address its shortcomings. Provides an overview of development banking in developing economies and examines the modus operandi of all Jamaica's post-Independence developmental institutions.